2008
DOI: 10.1111/j.1744-7429.2008.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Local Abundance and Distribution of Rain Forest Trees across Environmental Gradients in India

Abstract: We tested whether local abundance of rain forest trees in the medium elevation wet forests of the southern Western Ghats (WG) was related to environmental tolerance, life form, and geographical range. We selected trees in medium elevation wet forests (750-1700 m asl) of the southern WG, using two data bases: a small plot (30 × 30 m) data base of 288 species of trees (≥ 3 cm dbh) in 33 plots totaling 2.97 ha, and a data base of 135 species of tree (≥ 10 cm dbh) in larger plots of 1 ha each, totaling 4.84 ha. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…The relative success of taller species is in agreement with previous works focused on tropical forests at low elevations (Ruokolainen and Vormisto 2000; Davidar et al 2008;Kristiansen et al 2009). Overall, it seems that greater dispersal abilities associated with potentially higher individuals make the species to perform well at landscape level, which, in turn, could lead to high local abundances.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relative success of taller species is in agreement with previous works focused on tropical forests at low elevations (Ruokolainen and Vormisto 2000; Davidar et al 2008;Kristiansen et al 2009). Overall, it seems that greater dispersal abilities associated with potentially higher individuals make the species to perform well at landscape level, which, in turn, could lead to high local abundances.…”
Section: Discussionsupporting
confidence: 90%
“…In plants, studies have found that plant size is often correlated with species commonness at different scales: (1) At large scales across regions and continents, larger species have been found to be more widely distributed because of their greater dispersal ability (Ruokolainen and Vormisto 2000;Davidar et al 2008;Kristiansen et al 2009). (2) At local scales, large species could also be more abundant, because large plants have an advantage when they compete for light (Wright et al 2007) and tend to have higher reproductive success (Nathan and Muller-Landau 2000;Westoby et al 2002;; Aarssen et al 2006;Wright et al 2007;Kristiansen et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…; Macía & Svenning ) and that widespread species show broad environmental tolerances (Davidar et al. ; Slatyer et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Few have been tested rigorously in the context of Amazonian tree communities. Most researchers have found that common Amazonian species tolerate no broader edaphic or topographic variation than rare species (Phillips et al 2003, Tuomisto et al 2003a, Kinupp and Magnusson 2005see Jones et al 2008 for similar results from Costa Rica, and Davidar et al 2008 for a contrasting result from the Old World). First, we believe that tests to date of the idea that common Amazonian plant species tolerate a broader range of environmental conditions than rare ones (the niche breadth hypothesis of Brown [1984Brown [ , 1995) have not been suffi ciently rigorous to reject the idea.…”
Section: Hypothesismentioning
confidence: 99%